Association of genetic mutations and loss of ambulation in childhood‐onset dystrophinopathy. Issue 2 (17th November 2020) - Haber, Gregory; Conway, Kristin M.; Paramsothy, Pangaja; Roy, Anindya; Rogers, Hobart; Ling, Xiang; Kozauer, Nicholas; Street, Natalie; Romitti, Paul A.; Fox, Deborah J.; Phan, Han C.; Matthews, Dennis; et al.
Abstract: Background: Quantifying associations between genetic mutations and loss of ambulation (LoA) among males diagnosed with childhood‐onset dystrophinopathy is important for understanding variation in disease progression and may be useful in clinical trial design. Methods: Genetic and clinical data from the Muscular Dystrophy Surveillance, Tracking, and Research Network for 358 males born and diagnosed from 1982 to 2011 were analyzed. LoA was defined as the age at which independent ambulation ceased. Genetic mutations were defined by overall type (deletion/duplication/point mutation) and among deletions, those amenable to exon‐skipping therapy (exons 8, 20, 44–46, 51–53) and another group. Cox proportional hazards regression modeling was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Mutation type did not predict time to LoA. Controlling for corticosteroids, Exons 8 (HR = 0.22; 95% CI = 0.08, 0.63) and 44 (HR = 0.30; 95% CI = 0.12, 0.78) were associated with delayed LoA compared to other exon deletions. Conclusions: Delayed LoA in males with mutations amenable to exon‐skipping therapy is consistent with previous studies. These findings suggest that clinical trials including exon 8 and 44 skippable males should consider mutation information prior to randomization.